Design of Environmentally Friendly Air Conditioning System Based on Thermo Electric Peltier Tec1-12706 - Akbar Sujiwa (Journal FORTEI-JEERI, 2020)
Environmentally friendly problems have been widely studied in scientific journals, one of which is the use of gases that can damage the environment in a variety of cooling devices such as refrigerators and air conditioners (AC). In the past two decades, most of the refrigeration engines were still using Chloro Fluoro Carbons (CFC) gas, which had been researched in fact could damage the ozone layer. One alternative is to use freon gas to replace CFC gas as a component of air conditioning. Until now, CFC gas has been completely replaced by freon gas in the use of household appliances. But the use of this gas still has a bad side, especially for humans, when it inhaled in a certain amount can cause death. Therefore, in this study an air conditioning device with a main component was designed using thermoelectric TEC1-12706 which utilizes the Peltier effect in producing cold temperatures. This device is able to cooling a room with dimension 12 m2 in the interval of time 120 minutes to a temperature of 28.1 °C.